Study guides

☆☆

Q: -6 plus 4x plus 9-2x

Write your answer...

Submit

Related questions

2x + 3 = -92x = -12x = -6

8x + 5z - 4x + 3z + 6 = 8x - 4x + 5z + 3z - 6 = 4x + 8z - 6

-4x + 5 + 3x + 6 = -x + 11

It is -4x - 4

-6x-6 -or- -6(x+1)

4x + 2 + 6 = 2 4x + 8 = 2 4x = -6 x = -6/4 = -3/2

The answer to the math problem of 5x plus 7x-4x 6 is -12.

8x - 7y + 6

Because (x plus 3x) is 4x, and (-5 + 11) is 6.

6x+4 = x+12+4x-6 6x-x-4x = 12-6-4 x = 2

-4x + 2 = 6 -4x = 6 - 2 -4x = 4 x = 4 / -4 x = -1

if -4x+6=38 what x=

4x+6

-2x + 6 <= 4x + 18 -2x <= 4x + 12 -12 <= 6x -2 <= x

If the equasion is 12x+6-8x-4x-3+12 then the answer is 15.

Then the straight line equation is: y = -4x+6

7x+8

If your equation is 5x-2=4x+4 Then this is how you solve it... 5x-2=4x+4 5x-2+2=4x+4+2 5x=4x+6 5x-4x=4x-4x+6 x=6 Your x=6

5x + 6 = 1 / 4(13x-11)(5x+6)(4)(13x-11)= 14(65x2-55x+78x-66)=1260x2 +92x-264-1=0260x2+92x-263=0Graph y = 260x2 +92x -263 and find its zero or use the quadratic formula

4x+32=-4x+16x4x+32=12x-4x -4x32=8x/8 /84=x

x2 + 4x + 6 can not be factored. If you want, you can reduce it to an expression with a single x term by comleting the square: x2 + 4x + 6 = x2 + 4x + 4 + 2 = (x + 2)2 + 2

If you mean 49+6 = 4x-7 then the value of x is 15.5

4x+3y = 6 3y = -4x+6 y = -4/3x+2 in slope intercept form

7x + 6 - 4x = 5 + 2x + 7 subtract 6 from both sides and combine the 5 and 7 on the right: 7x - 4x = 2x + 6 subtract 2x from both sides and combine the 7x and -4x on the left: x = 6

2x + 3y + 4x + 9y = 2x + 4x + 3y + 9y = 6x + 12y which can be simplified to 6(x + 2y)

People also asked